The Relationship Between the Working Conditions of Nurses and Work Stress in the Hospital - Surtini, Surtini; Saputri, Berlian Yuli (Fundamental and Management Nursing Journal, 2020)
Introduction: Working conditions are a set of conditions for a company to work as employees in the environment. In this era of globalization the problems that often arise in the work environment include limited human resources, the number of nurses with patients who are not balanced or vice versa. Conditions like this that will have an impact on the psychological state of the nurse such as fatigue, emotion, boredom, mood swings and can lead to stress nurse work. Stress is a pressure or tension that is felt to endanger a person’s physical and psychological well-being. The bad impact can interfere with social interaction, both with colleagues, doctors and patients, so it can reduce work motivation which will affect the performance of nurses. The purpose of the study was to analyze the relationship between the working conditions of nurses and work stress in the hospital Method: This type of observational research, analytic design with cross sectional approach and data collection in this study using questionnaire instruments and observation sheets. The population of the study were all nurses implementing at ORPEHA Islamic General Hospital Tulungagung. Samples were taken with a quota sampling technique of 30 people. Data were analyzed by spearman rho test. Results: The result of this research is almost all of respondents stated that the condition of fun is about 27 people (90%) and almost all of the respondents do not experience stress, that is 26 people (86,7%). Spearman rho statistical test obtained P Value = 0.003 <0.05 so H0 is not accepted H1 accepted, which means there is a working relationship with working stress conditions nurses at the Islamic Hospital General ORPEHA Tulungagung 2017. Conclusion: Pleasant working conditions can avoid work stress for nurses. So that nurses can do their jobs optimally.